Loss of loop adenines alters human telomere d[AG3(TTAG3)3] quadruplex folding - Babinský, Martin; Fiala, Radovan; Kejnovská, Iva; Bednářová, Klára; Marek, Radek; Sagi, Janos; Sklenář, Vladimír; Vorlíčková, Michaela (Nucleic acids research, 2014)
Abasic (AP) lesions are the most frequent type of damages occurring in cellular DNA. Here we describe the conformational effects of AP sites substituted for 2'-deoxyadenosine in the first (ap7), second (ap13) or third (ap19) loop of the quadruplex formed in K(+) by the human telomere DNA 5'-d[AG3(TTAG3)3]. CD spectra and electrophoresis reveal that the presence of AP sites does not hinder the formation of intramolecular quadruplexes. NMR spectra show that the structural heterogeneity is substantially reduced in ap7 and ap19 as compared to that in the wild-type. These two (ap7 and ap19) sequences are shown to adopt the hybrid-1 and hybrid-2 quadruplex topology, respectively, with AP site located in a propeller-like loop. All three studied sequences transform easily into parallel quadruplex in dehydrating ethanol solution. Thus, the AP site in any loop region facilitates the formation of the propeller loop. Substitution of all adenines by AP sites stabilizes the parallel quadruplex even in the absence of ethanol. Whereas guanines are the major determinants of quadruplex stability, the presence or absence of loop adenines substantially influences quadruplex folding. The naturally occurring adenine-lacking sites in the human telomere DNA can change the quadruplex topology in vivo with potentially vital biological consequences.
Keywords: G-Quadruplexes; Adenine; Guanine; poškození DNA; DNA Damage; G-kvadruplexy; Models, Molecular; Telomere; draslík; Potassium; Humans; adenin; guanin; lidé; molekulární modely; telomery; Nuclear Magnetic Resonance, Biomolecular; nukleární magnetická rezonance biomolekulární